Energy and development in the periphery: A regional perspective on small hydropower projects. (March 2017) - Bere, Jemma; Jones, Calvin; Jones, Stuart; Munday, Max
Investments in renewable energy have been identified as one mechanism for encouraging development in lagging regions, with community owned or operated facilities potentially having a relatively greater impact. The development of small hydropower installations in Wales is examined to establish the economic and community benefits of such schemes. The sector displays a number of locally beneficial economic characteristics that are absent from larger scale renewable investments. However, this is shown to be a fragile sector dependent on a small number of key individuals and institutions, and with an investment model relying on depreciating UK government subsidies. Following an introduction, the paper first examines why renewables, and small-scale, community renewables in particular, have attracted attention as a part response to declining economic, social and environmental conditions in rural communities. It then describes the Welsh energy and policy context before describing the data and the method employed in the research. The paper then examines the economic value of small hydropower developments, the nature and scale of impacts on local social capital and on communities, and then the extent to which small hydropower might be considered distinct from other local energy sectors in terms of business behaviours and inter-organisation relationships. The discussion then focuses on factors affecting prospects for the small hydropower sector, and which will limit how far development of the sector can lead to transformative outcomes for communities close to the natural resource.